Productivity, Quality and Profitability of Okra (Abelmoschus esculentus) as Influenced by Organic Manures and Biofertilizers - Bamboriya, Jitendra Singh; Naga, S. R.; Sharma, S. R.; Choudhary, M. R.; Bamboriya, S. D. (International Journal of Bio-resource and Stress Management, 2018)
The present experiment was conducted at Horticultural Research Farm, Sri Karan Narendra College of Agriculture, Jobner, Rajasthan, India during kharif, 2017. The experiment was conducted in a randomized block design with sixteen treatments replicated thrice. The treatments include organic manures (control, FYM @ 20 t ha-1, vermicompost @ 6 t ha-1 and poultry manure @ 8 t ha-1) with biofertilizers (control, Azospirillum, PSB and Azospirillum+PSB). The results showed that application of vermicompost @ 6 t ha-1 significantly increased yield plant-1 (311.46 g), ha-1 (141.48 q) and picking-1 (6.11 kg) of okra. However, among the quality parameters the highest protein (1.97%) content and the lowest crude fiber content (1.54%) of fruit recorded under vermicompost which was at par with poultry manure. The highest nitrogen (0.315%), phosphorus (0.653%) and potassium (1.761%) content and uptake of nitrogen (45.81 kg ha-1), phosphorus (93.91 kg ha-1) and potassium (253.28 kg ha-1) also observed in vermicompost closely followed by poultry manure treatment. The maximum net returns (Rs 205928 ha-1) were obtained with vermicompost whereas poultry manure was superior in Benefit-cost ratio with the value 3.01. Among different biofertilizers combined use of Azospirillum+PSB recorded significantly higher yield (326.01 g plant-1, 134.91 q ha-1 and 5.83 kg picking-1) quality parameters (protein %); nitrogen, phosphorus, potassium content and uptake; net returns (` 207634 ha-1) and Benefit-cost ratio (3.36) of okra and the lowest crude fibre. Whereas superior values regarding the yields observed in the treatment receiving the combination of vermicompost @ 6 t ha-1 and Azospirillum+PSB.